Engineering Oleaginous Yeast as the Host for Fermentative Succinic Acid Production From Glucose - Babaei, Mahsa; Rueksomtawin Kildegaard, Kanchana; Niaei, Aligholi; Hosseini, Maryam; Ebrahimi, Sirous; Sudarsan, Suresh; Angelidaki, Irini; Borodina, Irina (Frontiers in Bioengineering and Biotechnology, 2019)
Oleaginous yeast Yarrowia lipolytica is a prospective host for production of succinic acid. The interruption of tricarboxylic acid cycle through succinate dehydrogenase gene (SDH) deletion was reported to result in strains incapable of glucose utilization and this ability had to be restored by chemical mutation or long adaptive laboratory evolution. In this study, a succinate producing strain of Y. lipolytica was engineered by truncating the promoter of SDH1 gene, which resulted in 77% reduction in SDH activity but did not impair the ability of the strain to grow on glucose. The flux towards succinic acid was further improved by overexpressing the genes in the glyoxylate pathway and the oxidative TCA branch, and expressing phosphoenolpyruvate carboxykinase from Actinobacillus succinogenes. A short adaptation on glucose reduced the lag phase of the strain and increased its tolerance to high glucose concentrations. The resulting strain produced 7.8±0.0 g/L succinic acid with a yield of 0.105 g/g glucose in shake flasks without pH control, while mannitol (11.8 ± 0.8 g/L) was the main by-product. Further investigations showed that mannitol accumulation was caused by low pH stress and buffering the fermentation medium eliminated mannitol formation. In a fed-batch bioreactor in mineral medium at pH 5, the strain produced 35.3 ± 1.5 g/L succinic acid with 0.26 ± 0.00 g/g glucose yield.